RANCANGAN BOOKLET BIOLOGI KELAS X SMA PADA MATERI PROTISTA - Fitria Adriani; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Booklet are print media in the form of leaflets or magazines that function as media to convey messages or information. A booklet is a small book that has at least five pages but no more than forty-eight pages outside the cover count. This study aims to determine the potential of booklet design in class X protista high school learning material. This research was conducted at the Binawidya Riau University in August-December 2020. The design of this booklet refers to the ADDIE development model, the stage used is only the analysis and design stage. The analysis stage was carried out by analyzing the 2013 curriculum and analyzing the learning material. The design stage is carried out by designing the syllabus and lesson plans first, then designing a booklet. Based on the results of the research on the design of biology booklet at KD 3.6 and 4.6, especially on Protista material, it can be used as teaching material for class X SMA.Key Words: Booklet, Protista